1996
DOI: 10.1002/(sici)1097-0142(19960801)78:3+<688::aid-cncr14>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and adjuvant therapy for patients with pancreatic carcinoma

Abstract: BACKGROUND Pancreatic cancer is a highly lethal disease with cc5% of patients surviving 5 years. There is no curative therapy for patients who cannot be surgically resected. Chemotherapy and radiation therapy can provide palliation but have not had a significant impact on 5‐year survival. METHODS Newer approaches for improving the survival of patients with pancreatic cancer integrating chemotherapy, radiation therapy, and surgery are being evaluated. New chemotherapeutic agents (e.g., gemcitabine, camptothecin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Previous studies revealed that the anti-tumor effect of 5-FU, CDDP and MMC was positively related with apoptosis induction [14][15][16] . Apoptosis is a form of programmed cell death regulated by some gene or other factors [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the anti-tumor effect of 5-FU, CDDP and MMC was positively related with apoptosis induction [14][15][16] . Apoptosis is a form of programmed cell death regulated by some gene or other factors [17] .…”
Section: Discussionmentioning
confidence: 99%